Infection by Giardia duodenalis among school-age children in the south of Mato Grosso - Caroline Dias Carrijo Rodrigues; João Gabriel Guimarães Luz; José Henrique Francisco Roma; Aline Pereira Marques; Lisie Souza Castro; Ludiele Souza Castro (Universidade de Santa Cruz do Sul, 2019)
Background and Objectives: Giardiasis represents a health public problem that may damage the physical and mental development, particularly of children. Therefore, the importance of performing the parasitological evaluation of this population and its determinants is highlighted. Thus, this study aimed to evaluate the prevalence and factors associated with Giardia duodenalis infection in children enrolled between the 1st and 3rd grades of primary education in two educational units in the south of Mato Grosso. Methods: After the consent of parents and children, the socioepidemiological questionnaire and the universal collector containing a preservative solution for the single fecal sample collection were handed out, which were analyzed by the spontaneous sedimentation technique. Results: Sixty participants with mean age of 7.05 years and male predominance (53.3%) were included. The overall prevalence of enteroparasites was 36.7%, of which 54.5% was infected by G. duodenalis. A significant association was found between the occurrence of this infection and the fact that the child belonged to the family that declared not having financial income (p = 0.04). Conclusion: G. duodenalis infection in school-age children persists and is associated with the absence of family financial income. These findings highlight the need to improve this population's living conditions, health education practices, and drug treatment access.